Reproducibility of pulmonary vein isolation guided by the ablation index: 1‐year outcome of the AIR registry. (11th May 2020) - Stabile, Giuseppe; Lepillier, Antoine; De Ruvo, Ermenegildo; Scaglione, Marco; Anselmino, Matteo; Sebag, Frederic; Pecora, Domenico; Gallagher, Mark; Rillo, Mariano; Viola, Graziana; Rossi, Luca; De Santis, Valerio; et al.
Abstract: Background: Ablation index (AI) is a new lesion quality marker that has been demonstrated to allow a high single‐procedure arrhythmia‐free survival in single‐center studies. This prospective, multi‐center study was designed to evaluate the reproducibility of pulmonary vein (PV) isolation guided by the AI. Methods: A total of 490 consecutive patients with paroxysmal (80.4%) and persistent AF underwent first time PV isolation and were divided in four study groups according to operator's preference in choosing the ablation catheter (a contact force (ST) or contact force surround flow (STSF) catheter) and the AI setting (330‐450 or 380‐500 at anterior wall or posterior wall, respectively). Results: At 12 months a high rate of freedom from AF recurrences was observed in patients with both paroxysmal and persistent AF (91% vs 83.3%;  P  = .039). There was no difference in the rate of AF recurrence among the four study groups (4.5% in group ST330‐450, 12.2% in group ST 380‐500, 14.9% in group STSF330‐450, 9.4% in group STSF380‐500;  P  = .083). Recurrence was also similar between patients treated with a ST (8%) or STSF catheter (12.1%;  P  = .2), and within patients targeting an AI settings of 330 to 450 (10.9%) or 380 to 500 (10.3%;  P  = .64). In patients with paroxysmal AF, there was no difference ( P  = .12) in the 1‐year freedom from AF recurrence among 14 operators that performed ≥10 ablation procedure. Conclusions: An ablation protocol respecting strict criteria for contiguity and quality lesion resulted in high rate of 1‐year freedom from AF recurrence, irrespective of the ablation catheters, AI settings, and operator.